2018
DOI: 10.1111/twec.12680
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism and international air travel: A gravity approach

Abstract: We present a theoretical model (adapted from the structural gravity model by Anderson and van Wincoop, American Economic Review, 93, 2003, 170) to capture the effects of terrorism on air passenger traffic between nations affected by terrorism. We then use equations derived from this model, in conjunction with alternative functional forms for trade costs, to estimate the effects of terrorism on bilateral air passenger service flows from 58 source countries to 26 destination countries during 2000–14. An addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Tourists may, however, be willing to accept the risk if the destination is exceptional enough to entice them (Frey, Luechinger, & Stutzer, 2007;Lepp & Gibson, 2003). In the same vein, a number of papers have shown that the effect of political instability/terrorism on tourism may be non-linear; that is, it starts adversely impacting tourism after reaching a certain threshold (Harb & Bassil, 2019;Mitra, Pham, & Bandyopadhyay, 2018;Saha & Yap, 2014). Sharifpour, Walters, and Ritchie (2013) and Morakabati and Kapu sci nski (2016) opine that risk appetite varies across tourist groups, from allocentric to psychocentric, and is mainly determined by the personality traits of tourists and the uniqueness of the destination.…”
Section: Tourism and Geopolitical Riskmentioning
confidence: 99%
“…Tourists may, however, be willing to accept the risk if the destination is exceptional enough to entice them (Frey, Luechinger, & Stutzer, 2007;Lepp & Gibson, 2003). In the same vein, a number of papers have shown that the effect of political instability/terrorism on tourism may be non-linear; that is, it starts adversely impacting tourism after reaching a certain threshold (Harb & Bassil, 2019;Mitra, Pham, & Bandyopadhyay, 2018;Saha & Yap, 2014). Sharifpour, Walters, and Ritchie (2013) and Morakabati and Kapu sci nski (2016) opine that risk appetite varies across tourist groups, from allocentric to psychocentric, and is mainly determined by the personality traits of tourists and the uniqueness of the destination.…”
Section: Tourism and Geopolitical Riskmentioning
confidence: 99%
“…Seminal papers by Enders and Sandler (1991), Enders, Sandler, and Parise (1992), Pizam and Mansfeld (1996), Sönmez (1998), Sönmez and Graefe (1998), Bonham, Edmonds, and Mak (2006), or Araña and Leon (2008) explored the impact of terrorism on tourism flows. Moreover, this topic still attracts a great deal of attention in the tourism economic literature (Bassil, Saleh, and Anwar 2017; Samitasa et al 2018; Goldman and Neubauer-Shani 2016; Walters, Wallin, and Hartley 2018; Mitra, Pham, and Bandyopadhyay 2018). In general, they obtained that terrorism-related incidents cause a significant decline in tourists’ intentions to visit those affected destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using bilateral tourism data, Llorca-Vivero (2008) finds that terrorism seriously damages the tourism industry, with particularly severe effects in developing countries. Focusing on air passenger service flows, Mitra, Pham, and Bandyopadhyay (2018) obtained that terrorism adversely impacts international air passenger travel. Neumayer and Plümper (2016) analyze spatial spillover effects in international tourism as a consequence of terrorism and find that attacks affect tourist flows not only to the targeted country but also to similar destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this case, tourists’ fear and their perception of risk will be aggravated leading to an unnecessary fall in tourist arrivals (Buigut and Amendah, 2016; Fletcher and Morakabati, 2008). Fourth, terrorism in a destination country reduces tourism flows via macroeconomic disruptions and its destructive effect on GDP (Mitra et al, 2018). Finally, terrorism can damage the image of a country, and frequent terrorist acts can alter the intentions of tourists to visit a destination (Alvarez and Campo, 2014; Fernando et al, 2013; Sönmez et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%